2013
DOI: 10.1590/0103-6440201302297
|View full text |Cite
|
Sign up to set email alerts
|

Storage Media For Avulsed Teeth: A Literature Review

Abstract: Dental avulsion is the most severe type of traumatic tooth injuries because it causes damage to several structures and results in the complete displacement of the tooth from its socket in the alveolar bone. The ideal situation is to replant an exarticulated tooth immediately after avulsion because the extraoral time is a determinant factor for treatment success and for a good prognosis. However, it is not always possible. The success of replantation depends on a number of factors that may contribute to acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0
48

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(177 citation statements)
references
References 55 publications
3
110
0
48
Order By: Relevance
“…The success of the treatment is extremely dependent on how the avulsed teeth were managed prior to replantation (8). Ideally, avulsed teeth should be immediately replanted (10). The rupture of the blood supply causes deterioration in different levels of the pulp and periodontal ligament (PDL) cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…The success of the treatment is extremely dependent on how the avulsed teeth were managed prior to replantation (8). Ideally, avulsed teeth should be immediately replanted (10). The rupture of the blood supply causes deterioration in different levels of the pulp and periodontal ligament (PDL) cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…Milk is a proven storage medium for avulsed teeth (6,8,11), but cell culture studies have shown that its effectiveness decreases over time (6)(7)(8), probably because the drop in its pH creates an unsuitable environment for cell survival (3). Thus, it was hypothesized that the renewal of milk for storing the avulsed tooth could prevent the drop in its pH.…”
Section: Discussionmentioning
confidence: 99%
“…Milk is recommended as a transport medium for avulsed teeth (3)(4)(5)(6)(7)(8)(9)(10)(11). Besides having low bacterial content (3,4), physiologic osmolality (230-270 mOsm/kg) and neutral pH (6.5-6.8), it provides the cells with nutrients (3) and growth factors (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Išsky-rus specialius tirpalus, skirtus danties saugojimui ir transportavimui, dažniausiai rekomenduojamas pasterizuotas pienas, kuris yra izotoninis skystis, turintis augimo faktorių, būtinų ląstelėms maistingų medžiagų, lengvai prieinamas, nebrangiai kainuojantis, su fiziologine pH verte ir osmotiškumu, o šie parametrai atitinka ant šaknies paviršiaus esančių periodonto raiščio ląstelių parametrus. Įvertinus visas charakteristikas, veiksmingumą ir pasiekiamumą, pienas pripažintas kaip tinkama ir gera terpė laikinam danties patalpinimui iki replantacijos, tuo tarpu išmušto danties laikymas sausai ar vandentiekio vandenyje lemia periodonto raiščio ląstelių, esančių ant danties šaknies paviršiaus, nekrozę [14,15]. Įrodyta, jog ilgas danties laikymas po avulsijos, ne fiziologinėje terpėje, yra vienas iš kritiškiausių faktorių ir sukelia visišką periodonto raiščio nekrozę, todėl gijimas, vykstant pakaitinei šaknies rezorbcijai, tampa vienintele išeitimi [16].…”
Section: Diskusijaunclassified
“…Išmuštą dantį galima gabenti vaiko burnos ertmėje, jei jis sąmoningas ir tai nesukels jam pavojaus [14]. Tokį atsakymą rinkosi daugelis bendrosios praktikos gydytojų ir pediatrų, kai didžioji dalis mokytojų atsakė priešingai.…”
Section: Diskusijaunclassified